Optimizing the Activities of Ganespo Library Assistants to Develop Book Management and Organizational Leadership Skills - Adhika Ikhsan Pratama; Rahmat Isnaeni Farhan; Syarifah; Halida Umami (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Libraries in modern Islamic boarding schools play an important role not only as centers of learning resources but also as spaces for developing students’ organizational and leadership capacities. This study examines how the activities of the Ganespo Library Assistants at Pondok Modern Darussalam Gontor contribute to the improvement of book management competencies and organizational leadership among students. The research employed a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, involving data reduction, data presentation, and conclusion drawing. The findings reveal that the optimization of library assistant activities was implemented through organized work programs, including task allocation, duty scheduling, collection inventory, borrowing services, bookshelf arrangement, and routine evaluations. These activities enhanced students’ discipline, accuracy, responsibility, teamwork, and managerial abilities. Furthermore, participation in the organization fostered leadership skills through collaborative decision-making, task delegation, and organizational coordination. The study also found that the library organization strengthened the literacy culture within the pesantren by improving students’ access to reading materials and learning resources. In conclusion, the Ganespo Library Assistant program functions as an effective medium for managerial training, character education, and leadership development in contemporary Islamic boarding school education.